The neolithic lithic industry at Tell Ain El-Kerkh - Arimura, Makoto (Excavation reports of Tell el-Kerkh, Northwestern Syria, 2020)
Northwest Syria during the Neolithic period has been less well studied than the rest of the northern Levant, where Neolithisation first took place in the Near East. The Neolithic Lithic Industry at Tell Ain El-Kerkh presents the first attempt to unveil the Neolithisation process in northwest Syria, with the techno-typological studies of the flintstone implements from Tell Ain el-Kerkh in the Rouj basin in Idlib, which was an important large Neolithic site occupied from the from the 9th to the 7th millennium BC. Examination of the lithic record from Tell Ain el-Kerkh revealed techno-morphological changes in flint tools during the long Neolithic sequence from the Early Pre-Pottery Neolithic B (PPNB) to the end of the Pottery Neolithic. The author interprets such changes in stone tools in the socio-economic context of the Neolithic.